2001
DOI: 10.1902/jop.2001.72.12.1726
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor‐β1 Autocrine Stimulation Regulates Fibroblast Proliferation in Hereditary Gingival Fibromatosis

Abstract: These results are consistent with the existence of an autocrine role of TGF-beta1 as a stimulator of HGF fibroblast proliferation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 34 publications
4
41
0
2
Order By: Relevance
“…6,7,[38][39][40] Our previous investigations showed that HGF fibroblasts are metabolically more active than normal fibroblasts. 5,8,24,25,41 In the present study, we have shown that both type I collagen and Hsp47 mRNA and protein levels were increased significantly in cultured HGF fibroblasts compared to NG fibroblasts. Furthermore, HGF fibroblasts with increased levels of type I collagen mRNA and protein also exhibited high levels of Hsp47.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…6,7,[38][39][40] Our previous investigations showed that HGF fibroblasts are metabolically more active than normal fibroblasts. 5,8,24,25,41 In the present study, we have shown that both type I collagen and Hsp47 mRNA and protein levels were increased significantly in cultured HGF fibroblasts compared to NG fibroblasts. Furthermore, HGF fibroblasts with increased levels of type I collagen mRNA and protein also exhibited high levels of Hsp47.…”
Section: Discussionsupporting
confidence: 48%
“…25 All HGF patients were members of the same family, and only fibrous and non-inflamed gingival tissue overgrowth were selected. The mean age of HGF group was 24.22 ± 6.38 years and included 3 males and 3 females.…”
Section: Cell Culturementioning
confidence: 99%
“…Heterodimerisation with TGF-h may affect both the availability, i.e. the local concentration, and the activity of TGF-h, an important mediator of fibroblast proliferation and synthesis of extracellular matrix components, particularly collagen and fibronectin [19]. Indeed, a substantial body of evidence points to an important role of TGF-h in myocardial remodelling and fibrosis in HF [20].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the similar inhibitory effects of TGF-␤1 and SLPI on IGFBP-3 expression are not entirely consistent with their opposing consequences on cell proliferation, although this apparent discrepancy might be related to the nature of the parental cell line (Ishikawa) utilized in this study. In a number of adenocarcinoma cell lines, abnormal TGF-␤ response could be generated in a gene-specific context (72)(73)(74). Finally, it would be of interest to ascertain whether other growth-regulatory genes mediate the proliferative effects of SLPI, and if their encoded products delineate sensitivity to SLPI in cell types other than the endometrial epithelial cells used here.…”
Section: Fig 8 Effects Of Tgf-␤1 On Ishikawa Cell Gene Expressionmentioning
confidence: 99%